Acute Myocardial Infarction on Contrast-Enhanced Computed Tomography - Akira Baba; Yumi Okuyama; Shinji Yamazoe; Takuji Mogami (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2016)
A 79-year-old man presented to our emergency department with sudden back pain. Laboratory results showed CK 2836 U/L (normal range 30-160), CK-MB 393 U/L (<25), D-dimer 1.4 μg/ mL (<1), BNP 37.9 pg/mL (<19.5), cTnl 0.133ng/mL (<0.028) and electrocardiogram showed ST elevation in V1~6. Acute myocardial infarction (AMI) was suspected. Because of the back pain, acute aortic dissection (AAD) and pulmonary thromboembolism (PE) needed to be ruled out and contrast-enhanced computed tomography (CECT) was performed.